The Economics of agriculture - Cohen, R L (New Delhi Mohit, 2000)
This book deals with the economics of agriculture in peace time. This book does not attemts analysis in full such as analysis would include the greater part of economic theory it is concerned to a large extent to point out the difference and those of indu
Keywords: Agriculture-Economic aspects-India; Economic development